Valve disease in chronic venous disorders: a quantitative ultrastructural analysis by transmission electron microscopy and stereology (Swiss Medical Weekly, 2013)
INTRODUCTION: The ultrastructure of venous valves and walls in chronic venous disease was investigated. METHODS: Consecutive patients were categorised into one of three groups (group A: patients with C1 venous disease in accordance with CEAP (Clinical severity, Etiology, Anatomy, Pathophysiology); group B: C2 and C3; group C: C4, C5 and C6). The terminal or preterminal valve and adjacent vessel wall was harvested from the great saphenous vein. Sections were examined with a transmission electron microscope. The volumes of elastin and of collagen per unit surface area of valve were assessed, as well as the surface endothelium of valve and vessel wall. RESULTS: The study population consisted of 17 patients. The elastin ratio was analysed by means of stereology. Mean values were: in group A, 0.45 μm3/m2; in group B, 0.67 μm3/m2; in group C, 0.97 μm3/m2. The ratio was similar for collagen (A, 15.7 μm3/m2; B, 26.8 μm3/m2; C, 30.1 μm3/m2). Surface analysis of the valve endothelium and the adjacent vessel wall endothelium showed a trend towards increasing damage with more severe disease. CONCLUSIONS: With progression of venous disease, the valve elastin content, assessed morphologically, seems to increase, and the endothelium of the venous valve and the vein wall tend to show more damage.